Capturing essentials in wound photography past, present, and future: A proposed algorithm for standardization. Issue 9 (September 2022) - Onuh, Ogechukwu C.; Brydges, Hilliard T.; Nasr, Hani; Savage, Elizabeth; Gorenstein, Scott; Chiu, Ernest
Abstract : Photographic documentation is indispensable in the management of chronic wounds. This article elaborates a standardized methodology for wound photography and aids clinicians in capturing consistent, high-fidelity images.